Effect of a model based on education and teleassistance for the management of obstetric emergencies in 10 rural populations from Colombia. (October 2022) - Escobar, María Fernanda; Echavarria, María Paula; Gallego, Juan Carlos; Riascos, Natalia; Vasquez, Hilda; Nasner, Daniela; Pabon, Stephanie; Castro, Zindy Alexandra; Cardona, Didier Augusto; Castro, Ana Milena; Ramos, Isabella; Hincapie, María Antonia; et al.
Introduction: Pregnant women and health providers in rural areas of low-income and middle-income countries face multiple problems concerning high-quality obstetric care. This study was performed to identify changes in maternal and perinatal indicators after implementing a model based on education and telecare between a high-complexity hospital in 10 low-complexity hospitals in a southwestern region of Colombia. Methods: A quasiexperimental study with a historic control group and without a pretest was conducted between 2017 and 2019 to make comparisons before and after obstetric emergency care through the use of teleassistance from 10 primary care centers to the referral center (Fundación Valle del Lili, FVL). Results: A total of 470 patients were treated before teleassistance implementation and 154 patients were treated after teleassistance implementation. After program implementation, the maternal clinical indicators showed a 65% reduction in the number of obstetric patients who were referred with obstetric emergencies. The severity of maternal disease that was measured at the time of admission to level IV through the Modified Early Obstetric Warning System score was observed to decrease. Conclusion: The implementation of a model based on education and teleassistance between low-complexity hospitals and tertiary care centers generated changes in indicators that reflect greater access to rural areas, lower morbidity at the time of admission, and a decrease in the total number of emergency events.